Soft Thermoplastic Elastomer for Easy and Rapid Spin‐Coating Fabrication of Microfluidic Devices with High Hydrophilization and Bonding Performances. Issue 2 (15th November 2018) - Lachaux, Julie; Salmon, Hugo; Loisel, Fanny; Arouche, Nassim; Ochoa, Ignacio; Fernandez, Luis L.; Uzan, Georges; Mercier, Olaf; Veres, Teodor; Roy, Emmanuel
Abstract: Spin‐coating process of a commercially available soft thermoplastic elastomer (sTPE) is demonstrated for the realization of microfluidic prototypes. It is a reliable, wrinkling‐free, and high‐yield holding and transfer methodology for single and multilayered devices fabrication. Complex microfluidic systems including embedded microlenses array, dilutor‐like chip for stable capillary filling, and pneumatically drive valve confirms the performances and quality of the process. The dissolved sTPE, a soft styrenic‐block polymer‐based material, is flexible in its raw state as poly(dimethylsiloxane) and thermoformable as classical thermoplastics. Depending on the solvent evaporation rate, two stable morphologies of the block nanodomains are revealed: either a nanocylinder or hexagonal nanospheres pattern. Both are evenly distributed over the whole surface and account for a uniform and convenient surface at a "microfluidic scale device." Plasma hydrophilization allows a stable and hydrophilic surface (≈20° after 7 d). The biocompatibility is assessed through the cell culture proliferation assay of progenitor endothelial cells. This sTPE solution displays fast and reliable fabrication and assembly performances, it can achieve strong and stable hydrophilicity within a low level of initial equipment investment. Abstract : Thermoplastic elastomers are increasingly used in microfluidics to meet the requirements of biologists and industrial translation. Discussion about a new formulation of a styrenic‐block copolymer dissolved for spin‐coating applications is presented. The material exhibits great potential for microfabrication and applications to life sciences. Thanks to its surface properties, biochip and multi‐level structures such as micro‐valve are easily demonstrated.